Review of food toxicological issues associated in rubber products - Ng, Mei Xiang; Ong, S.P.; Hii, C.L.; Chuah, L.A.; Law, C.L. (2014)
Over the centuries, rubber latex gained its popularity in machinery application due to its unique thermal properties, high elasticity and excellent impact resistance. It is widely accepted in food industry as rubber has good resistance to chemicals, including acids, alkalis and salts. For instance, rubber components comprise of couplings, shields, dust covers, gaskets and seals exist as group or standalone component in food manufacturing equipments or machinery. Even though most of the rubber based products in food industry fulfil the requirements of Food and Drug Administration (FDA), however, the presence of trace amount of chemicals upon the preceding processing of rubber might accidentally contaminate to the food products. The contamination that happened might caused changes in food quality in term of taste, smell or even visual appearance. Therefore, this paper aims to review some of the manufacturing process of natural rubber products and to understand the possibility of extractable and leachable contaminated food products. An overview of potential toxicological problems will be discussed and the finding will be summarized in this paper.